Advantages of FDM and gamma irradiation to manufacture personalized medical devices for airway obstructions - Aráoz, Beatriz; Bellía-Munzón, Gastón; Bousquet, Juan I.; Hermida, Élida B. (Frontiers in Bioengineering and Biotechnology, 2023)
In the early childhood population, congenital airway conditions like bronchomalacia (BM) can pose a life-threatening threat. A breakthrough technology called additive manufacturing, or 3D printing, makes it feasible to create a biomedical device that aids in the treatment of airway obstruction. This article describes how a polycaprolactone (PCL) splint for the upper airways can be created using the fusion deposition technique (FDM) and sterilized using gamma radiation. It is presented as a simple, accessible, and cost-reduced alternative that complements other techniques using more expensive and sophisticated printing methods. Thermomechanical and morphological analysis proved that FDM and sterilizing by gamma irradiation are both appropriate methods for producing splints to treat life-threatening airway blockages. Additionally, the 3D-printed splints’ effectiveness in treating a young patient with BM that was life-threatening was assessed by medical professionals. In this regard, the case report of a patient with 34 months of follow-up is presented. Splints manufactured by this affordable 3D printing method successfully surpass breathing arrest in life-threatening airway obstruction in pediatric patients. The success of this procedure represents a fundamental contribution to the treatment of the population in countries where access to expensive and complex technologies is not available.